ANALISIS KELAYAKAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) KERAJINAN TANGAN DI DESA PUTAT JAYA KECAMATAN SAWAHAN KOTA SURABAYA - Yuni Maulina; Muhammad Yasin (Jurnal Ekonomi Sakti, 2023)
This study aims to determine whether or not handicraft businesses, especially batik, are feasible or not in Putat Jaya Village. The method used is a qualitative approach and primary data sources. Data collection techniques using observation, interviews and documentation. By using various feasibility analyzes, namely cost analysis, revenue cost ratio (R/C), break event point (BEP), and return on investment (ROI). The results of this study are that all SMEs studied by calculating R/C> 1 are said to be feasible, BEP analysis has met even more than the minimum sales target, ROI is positive, which means that all capital spent is covered by business income so that the business is feasible to continue. From all the results of the feasibility analysis used, it shows that all MSME research informants are feasible to continue. Keywords: MSME, Handycraft, Batik, Business Feasibility Analys